Review and Systemizing of Financial Innovation Theoretical Approaches: Forming and Development Process - M. K. Khabekova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
Over the past decades the global fnancial system has undergone a number of major changes. The digitalization process has a major impact on the fnancial industry. One of the main features of this industry today is active innovation process. Financial innovations are a tool for improving the quality of fnancial system development in the context of global competition and globalization. However, the scientifc community still does not pay enough attention to empirical evidence of the impact of new fnancial instruments on the economy development. The article includes a review and systematization of theoretical approaches to the development of the term “fnancial innovations”, the concept of fnancial innovations and an assessment of their impact on the development of the fnancial system and the economy generally. The paper presents the defnitions and classifcation of fnancial innovations by scientists and researchers in this industry. Also discussed are argumentative issues about the characteristics and features of fnancial innovations.